2020
DOI: 10.1093/ageing/afaa197
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of virtual reality technology on functional mobility of older adults: systematic review and meta-analysis

Abstract: Background The accessibility, versatility and motivation provided by virtual reality technology (VRT) have fostered its rapid expansion as a rehabilitation technique to improve functional mobility. The aim of this study was to investigate the effectiveness of rehabilitation programmes using VRT, specific virtual reality technology (VRT-S) and non-specific virtual reality technology (VRT-NS), to improve functional mobility in individuals aged >60 years versus conventional treatment (CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…Multiple meta-analyses in HOA have synthesized evidence for significant improvements in executive functions ( Howes et al, 2017 ; Chen et al, 2020 ; Mansor et al, 2020 ) and working memory ( Mansor et al, 2020 ) in response to sequential or simultaneous motor-cognitive training while the evidence for global cognition [i.e., improvement ( Stanmore et al, 2017 ; Northey et al, 2018 ; Chen et al, 2020 ; Zhu et al, 2020 ; Gavelin et al, 2021 ) vs. no effect ( Wu et al, 2019 )] and learning and memory {i.e., mixed findings [improvement in updating memory but no effect on delayed memory ( Mansor et al, 2020 )]} remains conflicting, and no significant effects were synthesized for complex attention ( Vaportzis et al, 2019 ; Mansor et al, 2020 ), and verbal fluency ( Stanmore et al, 2017 ). Additionally, improvements in balance ( Howes et al, 2017 ; Pacheco et al, 2020 ) and functional exercise capacity ( Howes et al, 2017 ) have been synthesized while the evidence for mobility remains conflicting [i.e., improvement ( Pacheco et al, 2020 ; Gavelin et al, 2021 ) vs. no effect ( Howes et al, 2017 )] and no significant effects have been synthesized for activities of daily living ( Corregidor-Sánchez et al, 2020 ). When considering meta-analytic results for exergaming specifically, significantly larger improvements in complex attention ( Stanmore et al, 2017 ), executive functions ( Howes et al, 2017 ; Stanmore et al, 2017 ), global cognition ( Stanmore et al, 2017 ), visuospatial processing ( Stanmore et al, 2017 ), and also functional physical outcomes (i.e., balance, mobility) ( Howes et al, 2017 ), and fear of falling ( Howes et al, 2017 ), but not activities of daily living ( Corregidor-Sánchez et al, 2020 ) or functional exercise capacity ( Howes et al, 2017 ) have been synthesized compared to physically or cognitively active control interventions.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple meta-analyses in HOA have synthesized evidence for significant improvements in executive functions ( Howes et al, 2017 ; Chen et al, 2020 ; Mansor et al, 2020 ) and working memory ( Mansor et al, 2020 ) in response to sequential or simultaneous motor-cognitive training while the evidence for global cognition [i.e., improvement ( Stanmore et al, 2017 ; Northey et al, 2018 ; Chen et al, 2020 ; Zhu et al, 2020 ; Gavelin et al, 2021 ) vs. no effect ( Wu et al, 2019 )] and learning and memory {i.e., mixed findings [improvement in updating memory but no effect on delayed memory ( Mansor et al, 2020 )]} remains conflicting, and no significant effects were synthesized for complex attention ( Vaportzis et al, 2019 ; Mansor et al, 2020 ), and verbal fluency ( Stanmore et al, 2017 ). Additionally, improvements in balance ( Howes et al, 2017 ; Pacheco et al, 2020 ) and functional exercise capacity ( Howes et al, 2017 ) have been synthesized while the evidence for mobility remains conflicting [i.e., improvement ( Pacheco et al, 2020 ; Gavelin et al, 2021 ) vs. no effect ( Howes et al, 2017 )] and no significant effects have been synthesized for activities of daily living ( Corregidor-Sánchez et al, 2020 ). When considering meta-analytic results for exergaming specifically, significantly larger improvements in complex attention ( Stanmore et al, 2017 ), executive functions ( Howes et al, 2017 ; Stanmore et al, 2017 ), global cognition ( Stanmore et al, 2017 ), visuospatial processing ( Stanmore et al, 2017 ), and also functional physical outcomes (i.e., balance, mobility) ( Howes et al, 2017 ), and fear of falling ( Howes et al, 2017 ), but not activities of daily living ( Corregidor-Sánchez et al, 2020 ) or functional exercise capacity ( Howes et al, 2017 ) have been synthesized compared to physically or cognitively active control interventions.…”
Section: Case Studymentioning
confidence: 99%
“…Additionally, improvements in balance ( Howes et al, 2017 ; Pacheco et al, 2020 ) and functional exercise capacity ( Howes et al, 2017 ) have been synthesized while the evidence for mobility remains conflicting [i.e., improvement ( Pacheco et al, 2020 ; Gavelin et al, 2021 ) vs. no effect ( Howes et al, 2017 )] and no significant effects have been synthesized for activities of daily living ( Corregidor-Sánchez et al, 2020 ). When considering meta-analytic results for exergaming specifically, significantly larger improvements in complex attention ( Stanmore et al, 2017 ), executive functions ( Howes et al, 2017 ; Stanmore et al, 2017 ), global cognition ( Stanmore et al, 2017 ), visuospatial processing ( Stanmore et al, 2017 ), and also functional physical outcomes (i.e., balance, mobility) ( Howes et al, 2017 ), and fear of falling ( Howes et al, 2017 ), but not activities of daily living ( Corregidor-Sánchez et al, 2020 ) or functional exercise capacity ( Howes et al, 2017 ) have been synthesized compared to physically or cognitively active control interventions.…”
Section: Case Studymentioning
confidence: 99%
“…Exergaming interventions were shown to be a feasible and effective training approach in healthy older people; with high adherence to exergame interventions (>90%) and only rare and minor adverse events being reported ( Valenzuela et al, 2018 ). In addition to this, exergaming interventions have positive effects on physical and cognitive functioning such as balance, functional mobility, gait and executive functions in healthy older adults ( Stanmore et al, 2017 ; Corregidor-Sánchez et al, 2020a , b ; Fang et al, 2020 ; Pacheco et al, 2020 ; Wollesen et al, 2020 ), as well as people suffering from chronic diseases ( Bonnechère et al, 2016 ; Stanmore et al, 2017 ; Zeng et al, 2017 ). However, some current gaps in knowledge need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is a lack of research on the use of serious games or VR for the treatment of neck pain in this population [ 14 ]. Previous research has suggested that VR technology could improve variables such as functional mobility through improving gait quality and resistance in older populations [ 20 ]. A recent systematic review also suggested that VR interventions have the potential to improve health outcomes in older adults.…”
Section: Introductionmentioning
confidence: 99%